2010
DOI: 10.3758/s13414-010-0065-7
|View full text |Cite
|
Sign up to set email alerts
|

Increases in rewards promote flexible behavior

Abstract: Offering reward for performance can motivate people to perform a task better, but better preparation for one task usually means decreased flexibility to perform different tasks. In six experiments in which reward varied between low and high levels, we found that reward can encourage people to prepare more flexibly for different tasks, but only as it increased from the level on the previous trial. When the same high rewards were offered continuously trial after trial, people were more inclined to simply stick w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

11
99
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 84 publications
(110 citation statements)
references
References 47 publications
11
99
0
Order By: Relevance
“…Some previous research has suggested that consistent levels of reward increase the stability of cognitive control (versus the flexibility; Mueller et al, 2007) and therefore specifically improve performance in repeat trials. However, reward-related improvements in Experiment 3 were largely restricted to switch trials (similar to the results obtained by Shen & Chun, 2011), evident as a reduction of the switch cost and increased memory selectivity for items appearing on those trials, which suggests that the effect of reward on cognitive control might be more complex and situation dependent: The fact that reward benefited switch trials more than repeat trials could suggest that repeat-trial performance was already at a peak, even without reward, and that reward increased performance especially in switch trials.…”
Section: Discussionsupporting
confidence: 79%
“…Some previous research has suggested that consistent levels of reward increase the stability of cognitive control (versus the flexibility; Mueller et al, 2007) and therefore specifically improve performance in repeat trials. However, reward-related improvements in Experiment 3 were largely restricted to switch trials (similar to the results obtained by Shen & Chun, 2011), evident as a reduction of the switch cost and increased memory selectivity for items appearing on those trials, which suggests that the effect of reward on cognitive control might be more complex and situation dependent: The fact that reward benefited switch trials more than repeat trials could suggest that repeat-trial performance was already at a peak, even without reward, and that reward increased performance especially in switch trials.…”
Section: Discussionsupporting
confidence: 79%
“…Importantly, however, a reward by threat interaction was present, such that the slowing of RT by irrelevant threat stimuli that was observed during no-reward was eliminated during reward. Recently, several studies have reported specific effects of motivation during diverse perceptual and cognitive tasks (Engelmann & Pessoa, 2007; Krebs, et al, 2010; Savine, et al, 2010; Shen & Chun, 2011). In a recent fMRI study, we showed that monetary reward cues presented prior to the task phase reduced both interference and facilitation behavioral scores in a response conflict task, suggesting that motivation reduced the influence of task-irrelevant (neutral) words (Padmala & Pessoa, 2011).…”
Section: Discussionmentioning
confidence: 99%
“…For example, positive incentives such as monetary reward improve performance across a diverse set of perceptual and cognitive tasks (Engelmann & Pessoa, 2007; Krebs et al, 2010; Savine et al, 2010; Shen & Chun, 2011). At the same time, task-irrelevant negative stimuli have detrimental effects on performance during related tasks (Dolcos & McCarthy, 2006; Erthal et al, 2005; Hartikainen et al, 2000; Padmala et al, 2011).…”
Section: Introductionmentioning
confidence: 99%
“…Even trialto-trial feedback is rarely provided, a choice that follows the lead of three studies that laid the methodological foundations of this work (Allport et al, 1994;Meiran, 1996;Rogers and Monsell, 1995 -only Meiran's Experiment 4 included trial-to-trial feedback of any kind). Given this, it is perhaps not surprising that few studies since have explicitly manipulated action outcomes in task switching, with the notable exception of experiments using adaptations of the Wisconsin Card Sorting Task in which subjects must use trial-to-trial feedback to infer a sorting rule (e.g., Monchi et al, 2001;Rogers et al, 1998) and a handful of studies using reward incentives to motivate effective switching (Kleinsorge and Rinkenauer, 2012;Nieuwenhuis and Monsell, 2002;Shen and Chun, 2011). References to feedback and action outcomes are notable by their absence in recent authoritative reviews of task-switching research (Grange and Houghton, 2014;Kiesel et al, 2010;Vandierendonck et al, 2010) as well as in the related research literatures on response conflict (MacLeod, 1991;Yeung, 2013) and response inhibition (Aron et al, 2014).…”
Section: Concrete Goals and Sequential Actionsmentioning
confidence: 98%